ANTIBACTERIAL EFFECT OF KELAKAI LEAF EXTRACT (STENOCHLAENA PALUSTRIS (BURM) BEDD.) FOR INHIBITING ENTEROCOCCUS FAECALIS - Firdaus, I Wayan Arya Krishnawan; Dewi, Nurdiana; Fuady, Ridwan Ichshalul; Apriasari, Maharani Laillyza (Odonto : Dental Journal, 2022)
Background: Root canal treatment is a stage of treating pulp infection by removing the necrotic tissue and eliminating microorganisms. Inadequate sterilization cause persistent root canal bacteria, including Enterococcus faecalis. The irrigation solution that has become the gold standard in root canal treatment is Sodium hypochlorite but it has some weaknesses. Kelakai leaf extract can be an alternative root canal irrigation because it has minimal side effects and antibacterial compounds such as flavonoid, saponin, alkaloid, and tannin.Methods: This research was a true experimental laboratory with posttest only and control group design. The research using 5 treatment groups with 3 replications, so that total sample was 15 samples. Group 1-4 were kelakai leaf extract concentrations of 25%, 50%, 75%, 100% and group 5 was Sodium hypochlorite 2,5%. The parameter measured was the diameter of the inhibition zone (mm) formed on MHA.Results: One Way Anova and Post Hoc LSD test results showed a significant difference between each treatment group of kelakai leaf extract compared with Sodium hypochlorite 2,5%. Kelakai leaf extract 25%, 50%, 75%, 100% concentrations, and Sodium hypochlorite 2,5% had an average inhibition zone diameter which were 9.47 mm, 14.64 mm, 17.91 mm, 21.24 mm, and 23.27 mm.Conclusion: Kelakai leaf extract concentrations of 25%, 50%, 75%, and 100% had inhibitory activity against Enterococcus faecalis but had not been equivalent to Sodium hypochlorite 2,5%.